2021
DOI: 10.1021/acs.inorgchem.1c01896
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of closo-CB11H12 Salts Using Common Laboratory Reagents

Abstract: Lithium and sodium salts of the closo-carbadodecaborate anion [CB 11 H 12 ] − have been shown to form stable solidstate electrolytes with excellent ionic conductivity for all-solid-state batteries (ASSB). However, potential commercial application is currently hindered by the difficult, low-yielding, and expensive synthetic pathways. We report a novel and cost-effective method to synthesize the [CB 11 H 12 ] − anion in a 40% yield from [B 11 H 14 ] − , which can be synthesized using common laboratory reagents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Finally, it has been shown that, even though in a nonoptimized system, MM-NCB allows sodium to be reversibly plated/stripped at rt, withstanding decent current densities in comparison with the specific capacities of commonly employed Na-positive electrodes. Such findings prove that the destabilization driving fast ion motion in large-cage hydroborates is not necessarily achieved by further anion mixing, but can be achieved even starting from a unique and cheap precursor, by tuning the stabilization of nonequilibrium disordered phases.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, it has been shown that, even though in a nonoptimized system, MM-NCB allows sodium to be reversibly plated/stripped at rt, withstanding decent current densities in comparison with the specific capacities of commonly employed Na-positive electrodes. Such findings prove that the destabilization driving fast ion motion in large-cage hydroborates is not necessarily achieved by further anion mixing, but can be achieved even starting from a unique and cheap precursor, by tuning the stabilization of nonequilibrium disordered phases.…”
Section: Discussionmentioning
confidence: 82%
“…However, the synthesis of Na 11 (B 11 H 14 ) 3 (B 11 H 13 ) 4 reported here requires only the use of wet chemistry approaches and common laboratory consumables, which may be more cost-effective than when compared to the majority of the syntheses reported for carboranes. 67…”
Section: Resultsmentioning
confidence: 99%
“…reported here requires only the use of wet chemistry approaches and common laboratory consumables, which may be more cost-effective than when compared to the majority of the syntheses reported for carboranes. 67 The oxidative stability limit of Na 2 B 11 H 13 was determined to be 2.1 V against Na metal based on the anodic peak observed in its linear sweep voltammogram at 30 °C (Fig. S13 †).…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…These superionic results observed for a-LiB 11 -H 14 $(H 2 O) n between 60 and 90 C also correlate to the results observed for the 0.7Li(CB 9 H 10 )-0.3Li(CB 11 H 12 ) mixture, 35 of which, to date, is the lithium boron-hydrogen sample with the highest ionic conductivity at room temperature (6.7 Â 10 À3 S cm À1 ). It is important to highlight that carboranes are more expensive and more difficult to synthesise than carbon free boron-hydrogen salts, 44 such as a-LiB 11 H 14 $(H 2 O) n reported here.…”
Section: Sample Characterisationmentioning
confidence: 96%
“…32 Some of the most promising lithium-boranes as solid-state electrolytes have carboranes in their structure, such as 0.7Li(CB 9 H 10 )-0.3Li(CB 11 H 12 ) and Li 3 (B 11 H 14 )(CB 9 H 10 ) 2 , which present ionic conductivities higher than 1 Â 10 À3 S cm À1 at 25 C. 32,35 However, carboranes usually present high-costs due to the need for expensive and dangerous reagents, as well as, long synthetic processes. 44,45 The optimisation of synthetic processes of metal-boranes with reduced costs is important for further research and application as solid-state electrolyte.…”
Section: Introductionmentioning
confidence: 99%